Converting hip and knee arthroplasty cases to same- day surgery due to COVID-19. (2021) - Cherry, A.; Montgomery, S.; Brillantes, J.; Osborne, T.; Khoshbin, A.; Daniels, T.; Ward, S. E.; Atrey, A.
No abstract available